2021
DOI: 10.1001/jamacardio.2020.5969
|View full text |Cite
|
Sign up to set email alerts
|

Association of Low Plasma Transthyretin Concentration With Risk of Heart Failure in the General Population

Abstract: IMPORTANCE Several lines of evidence support low plasma transthyretin concentration as an in vivo biomarker of transthyretin tetramer instability, a prerequisite for the development of both wild-type transthyretin cardiac amyloidosis (ATTRwt) and hereditary transthyretin cardiac amyloidosis (ATTRm). Both ATTRm and ATTRwt cardiac amyloidosis may manifest as heart failure (HF). However, whether low plasma transthyretin concentration confers increased risk of incident HF in the general population is unknown.OBJEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…In agreement with the association between low circulating levels of transthyretin and cardiovascular disease [ 39 , 40 ], we detected lower expression of transthyretin in exosomes of STEMI than in those of CCS patients. Conversely to the higher level of circulating ceruloplasmin found in myocardial infarction patients, exosomes isolated from STEMI displayed a reduced level of ceruloplasmin, suggesting that exosome protein expression does not necessarily reflect circulating free-form levels of this positive acute-phase protein [ 20 , 39 ]. Interestingly, changes in plasma exosome-associated inflammatory proteins, including ceruloplasmin, have been recently reported also in CABG and HSV patients [ 9 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In agreement with the association between low circulating levels of transthyretin and cardiovascular disease [ 39 , 40 ], we detected lower expression of transthyretin in exosomes of STEMI than in those of CCS patients. Conversely to the higher level of circulating ceruloplasmin found in myocardial infarction patients, exosomes isolated from STEMI displayed a reduced level of ceruloplasmin, suggesting that exosome protein expression does not necessarily reflect circulating free-form levels of this positive acute-phase protein [ 20 , 39 ]. Interestingly, changes in plasma exosome-associated inflammatory proteins, including ceruloplasmin, have been recently reported also in CABG and HSV patients [ 9 ].…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, among the acute-phase proteins investigated in our study, only transthyretin and ceruloplasmin discriminated between STEMI and CCS patients. These two proteins have been associated with cardiovascular diseases [22,[39][40][41] and used as markers of inflammation. Indeed, during the acute-phase response/increased inflammation, the plasma level of ceruloplasmin increases, whereas the concentration of transthyretin drops [29,[42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…The decline in serum TTR portended worse survival in wild-type ATTR-CA patients, which was considered as an independent predictor of OS in patients with transthyretin amyloidosis ( 26 ). A Danish cohort study including 16,967 individuals demonstrated that lower serum TTR concentrations indicated a risk of incident HF ( 27 ). Also, patients with higher tetrameric TTR tend to respond better to TTR kinetic stabilizers ( 28 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, TTR is a negative acute-phase protein, and patients with severe sepsis often have very low TTR concentrations [50]. Recently, low plasma transthyretin concentration has been shown to associate with incident heart failure in the general population [51], and it is suggested that low plasma TTR levels could be a biomarker of transthyretin tetramer instability [52]. Increasing evidence supports the view that TTR tetramers, under unbalanced homeostatic conditions, dissociate in misfolded monomers that tend to aggregate and fibrillate and, after infiltrating the cardiac extracellular matrix, induce oxidative stress and mitochondrial damage and increase cardiac wall thickness and diastolic dysfunction [53].…”
Section: Discussionmentioning
confidence: 99%